1979
DOI: 10.1037/h0081734
|View full text |Cite
|
Sign up to set email alerts
|

Infant perceptual, cognitive, and motor behaviours as predictors of subsequent cognitive and language development.

Abstract: The purpose of this study was to examine the relationship between infant abilities and subsequent cognitive and language development. In a longitudinal study, 80 preterm and 68 full-term infants were administered the Bayley Scales at 4, 8,12,18, and 24 months, the Uzgiris-Hunt Scale at 4, 8, 12, and 18 months, the Caldwell Inventory of Home Stimulation (HOME) at 12 months, the Reynell Language Scales at 24, 30, and 36 months, and the Stanford-Binet at 30 and 36 months. There were significant correlations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The mental scale measures children’s early cognitive development, including communication skills, expressive and receptive vocabulary, comprehension, and problem-solving skills. Siegel (1979) found that low Bayley test scores in infancy predicted low scores on cognitive, language, perceptual, and visual motor tests later in childhood. The revised Bayley Scale (BSID-II), from which the BSF-R has been developed, has been found to be a valid measure of IQ that correlates positively with other IQ measures (Nellis and Gridley 1994).…”
Section: Methodsmentioning
confidence: 94%
“…The mental scale measures children’s early cognitive development, including communication skills, expressive and receptive vocabulary, comprehension, and problem-solving skills. Siegel (1979) found that low Bayley test scores in infancy predicted low scores on cognitive, language, perceptual, and visual motor tests later in childhood. The revised Bayley Scale (BSID-II), from which the BSF-R has been developed, has been found to be a valid measure of IQ that correlates positively with other IQ measures (Nellis and Gridley 1994).…”
Section: Methodsmentioning
confidence: 94%
“…The most important caveat is that the findings do not establish a causal relationship between prenatal cocaine exposure and later developmental delays. Although motor development, compared with language or social skills, appears to have a greater neurobiologic basis and may be relatively less affected by cultural factors [39][40][41][42] , the environment in which the children are raised will influence the rate and level of motor development. This point is most evident in the relatively low correlations between birth and maternal variables and motor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…42 The BSID at 4, 8, 12, 18, and 24 months is correlated with Stanford-Binet Intelligence Scales at 30 and 36 months, with the perceptual items being more predictive at early months. 44 The MDI at 2 years is correlated with the Stanford-Binet IQ at 3 and 5 years. 45 No study was performed on a night when a child had an acute illness such as fever or nasal discharge.…”
Section: Developmental Assessmentmentioning
confidence: 99%